2007
DOI: 10.1016/j.jpsychores.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Depression following pegylated interferon-alpha: Characteristics and vulnerability

Abstract: Objective: Interferon-α2 (IFN-α) injections may be capable of triggering depression in some individuals. The first objective was to further characterize this depression, and secondly to examine whether pre-treatment temperament was correlated with subsequent vulnerability to IFN-α.Methods: Twenty-three initially euthymic adults undergoing year-long PEG-IFN-α treatment for hepatitis C were evaluated at baseline and then prospectively monitored using both the Structured Clinical Interview for DSM-IV (SCID) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 56 publications
8
82
0
2
Order By: Relevance
“…Most studies investigating the role of personality in depression have not reported any major effects of agreeableness (Bienvenu et al, 2004;Kendler et al, 2006). However, indirect evidence suggests that lower agreeableness predicts the development of depression in various patient groups including adolescents who suffered severe burns in early childhood (Liber et al, 2008), adults undergoing interferon-alpha treatment for hepatitis C (Lotrich et al, 2007), and patients with chronic kidney disease (Hoth et al, 2007). Finch and Graziano (2001) demonstrated that agreeableness exerts its effects on depression exclusively through social exchange such as social support and social conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating the role of personality in depression have not reported any major effects of agreeableness (Bienvenu et al, 2004;Kendler et al, 2006). However, indirect evidence suggests that lower agreeableness predicts the development of depression in various patient groups including adolescents who suffered severe burns in early childhood (Liber et al, 2008), adults undergoing interferon-alpha treatment for hepatitis C (Lotrich et al, 2007), and patients with chronic kidney disease (Hoth et al, 2007). Finch and Graziano (2001) demonstrated that agreeableness exerts its effects on depression exclusively through social exchange such as social support and social conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Depression with varying severity and associated symptoms, such as insomnia, irritability, cognitive decline and suicidal ideation occur with IFN therapy (69)(70)(71). While certain studies have hypothesized that incidence of major depression remains the same in patients treated with IFN as compared to the general population (72), others indicate that major depression may be induced by the treatment, even in subjects without a previous history of major depression (73). This may lead to a cessation of treatment or reduction of dosage, which affects the course of recovery.…”
Section: Depressive-like Behavior Induced By Chemotherapymentioning
confidence: 99%
“…These models have been somewhat conclusive in providing the evidence that depression precedes degenerative diseases. In addition, the studies indicate that degeneration is nothing but the consequence of neuroinflammation (70)(71)(72)(73)(74)(75)(76)(77)(78). In one such instance, a non-toxic dose of bacterial endotoxin that resulted in increased secretion of cytokines, as well as activation of microglia, also resulted in extended loss of dopaminergic neurons to a subsequent suboptimal inflammatory stimulus (6-hydroxydopamine).…”
Section: Cytokine-associated Depressive Symptoms and Neurodegenerationmentioning
confidence: 99%
“…This clinical situation has become a paradigmatic model for prospectively examining vulnerability/resilience to inflammatory cytokine-associated depression, as MDD develops in about 30% of non-depressed subjects within a few months of initiating IFN-a treatment (IFN-MDD) (Lotrich, 2009;Raison et al, 2005). A number of putative vulnerability factors for subsequent IFN-MDD have been identified ranging from a 'short' (S) low-expression allele in the promoter of the serotonin transporter (5-HTTLPR) (Bull et al, 2008;Lotrich et al, 2009), a polymorphism in the serotonin 1A receptor (Kraus et al, 2007), increased interleukin-6 (IL-6) serum levels and an IL-6 polymorphism (Bull et al, 2008;Prather et al, 2009), pre-existing poor sleep quality (Franzen et al, 2009), high neuroticism traits (Lotrich et al, 2007), increased hypothalamic-pituitaryadrenal axis sensitivity, (Raison et al, 2008), elevated ratio of omega-6 fatty acids to omega-3 fatty acids , and increased sensitivity to activating the p38 mitogen-activated protein kinase (Felger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%